(Life) Science Funding in Switzerland (2)§ - Mauro Dell'Ambrogio (CHIMIA, 2016)
In comparison with other European countries, Switzerland is very well positioned in terms of research funding and output thanks to a large part to the approx. 7 billion CHF annually with which the Swiss Federal Government funds education, research and innovation.